Uji Aktivitas Antibakteri Ekstrak Etanol Bawang Putih (Allium sativum) terhadap Pertumbuhan Bakteri Salmonella typhii dan Shigella dysenteriae - Gyidian Upa; Agusalim Ali; Yenti Purnamasari (Halu Oleo University, 2017)
ABSTRACT Diseases of gastrointestinal infections, especially those caused by the bacterium Salmonella typhii and Shigella dysenteriae still a health problem in Indonesia. Garlic (Allium sativum) is a traditional medicine which has antibacterial properties. Garlic contains Allisin, alkaloids, tannins and saponins. The purpose of this study was to determine the antibacterial activity of ethanol extract of the bulbs of garlic (Allium sativum) on the growth of the bacteria Salmonella typhii and Shigella dysenteriae. This study is experimental with post test only control group design. Test of inhibition is determined based on the diameter of clear zone formed. Testing was performed against a pure extract of garlic, the positive control, negative control and solvent control for comparison. Each treatment is performed three times. The results showed that the ethanol extract of garlic (Allium sativum) does not produce a clear zone well against Salmonella typhi and Shigella dysenteriae, it can be concluded that the ethanol extract of garlic (Allium sativum) has no antibacterial activity against Salmonella typhii and Shigella dysenteriae. It is recommended to use another method to extract further research as the development or continuation of this research Keywords: Antibacterial activity, garlic(Allium sativum), Salmonella typhi, Shigella dysenteriae.